Affecting Factors Smoking Cessation Intention among Adolescent E-Cigarette Smokers - Pitaloka, Ananda Khoirunnisa Dewanti; Etrawati, Fenny; Hadirama, Sakinah (Poltekkes Kemenkes Tanjung Karang, 2023)
The prevalence of e-cigarette smoking in Palembang City reached 3.2% in 2018. Adolescent e-cigarette smokers in Palembang City have a reasonably firm intention to quit smoking e-cigarettes. Quitting e-cigarette smoking is a stage that starts with forming self-intention so that one can maintain new habits. This study aims to determine the factors influencing the intention to quit smoking e-cigarettes in Palembang City adolescents. This study used a quantitative approach with a cross-sectional research design. The research sample was calculated using the two proportions difference hypothesis test formula, totaling 134 adolescents aged 10-24 years. The analysis used was univariate, bivariate analysis using a chi-square test, and multivariate analysis with multiple logistic regression test prediction model. The results showed a relationship between the age of first e-cigarette smoking (p=0.002), knowledge (p